Searching for gallium bioactive compounds: Gallium(III) complexes of tridentate salicylaldehyde semicarbazone derivatives - Gambino, Dinorah; Fernandez, Mariana; Santos, Diego; Etcheverria, Gustavo A.; Piro, Oscar E.; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Tomaz, Isabel; Marques, Fernanda (Pergamon-Elsevier B.V. Ltd, 2011)
In the search for gallium bioactive compounds five Ga(III) complexes, [Ga(III)(L-H)(2)](NO(3)), with tridentate salicylaldehyde semicarbazone derivatives as ligands (L) have been synthesized and characterized in the solid state and in solution by different techniques. The crystal structure of [Ga(III)(L4-H)(2)](NO(3))center dot 2H(2)O, where L4 is 3-ethoxysalicylaldehyde semicarbazone, was solved by X-ray diffraction methods. The gallium(III) ion is in a distorted octahedral environment, coordinated to two nearly planar and mutually perpendicular 3-ethoxysalicylaldehyde semicarbazonato anions acting as tridentate ligands through their phenol and carbonyl oxygen atoms and their azomethine nitrogen atom. Their biological potential has been explored by evaluating their activity on Mycobacterium tuberculosis, causative agent of tuberculosis, and their cytotoxicity on tumor cell lines. Three different human tumor cell lines were selected that show different degrees of resistance to metallodrugs: ovarian A2780 (low resistance), breast MCF7 (medium resistance) and prostate PC3 (high resistance) cells. Although the complexes have not shown activity on M. tuberculosis, complexation with gallium has led to the enhancement of the cytotoxic potencies of the organic compounds. Those complexes that contain a bromide substituent at the phenolate ring have shown the highest cytotoxicities. In particular, [Ga(III)(L2-H)(2)](NO(3)), where L2 is 5-bromosalicylaldehyde semicarbazone, has shown a remarkable cytotoxicity on A2780 tumor cell line with an IC(50) value of the same order than cisplatin (IC(50) (Ga-L2) = 2.4 +/- 0.3 mu M; IC(50) (cisplatin) = 2.0 +/- 0.1 mu M, 72 h incubation at 37 degrees C). Interestingly, this complex has also shown moderate cytotoxicity against MCF7 and PC3 cells (IC(50) (MCF7) = 30 +/- 6; IC(50) (PC3) = 18 +/- 3 mu M). Therefore, this gallium compound could be considered a promising wide spectrum potential anti-tumor agent. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Gallium complexes; Salicylaldehyde semicarbazones; ONO donors; Anti-tumor; Anti-mycobacteria